BUILDING AN ASSET PERFORMANCE FRAMEWORK IN OPTIMISING THE MANAGEMENT OF LAND AND BUILDING ASSET UTILISATION IN JOMBANG REGENCY - Aini, Intan Nor; Abdurrochim, Muhammad; Negoro, Abul Haris Suryo (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
This study aims to optimize the management of land and building asset utilization to increase local revenue in Jombang Regency, based on the building asset performance framework. Asset management by local government organizations includes inventory, valuation, and legal audits, which significantly affect the effectiveness and efficiency of asset utilization. The method used is a descriptive qualitative approach, employing data collection techniques such as observation, interviews, and documentation studies. This approach was chosen because it allows researchers to explore the processes, policies, challenges, and strategies undertaken by government agencies in managing regional assets more comprehensively and contextually. Data analysis techniques were carried out by reducing data, presenting data, and drawing conclusions. The results showed that the optimization of land and building asset utilization management in Jombang Regency has not met the target for revenue realization from the utilization of regional assets in the 2024 APBD post, resulting in a realization gap ranging from 0% to 270%. Synergy in the institutional administration process is a crucial factor in asset utilization. This is because there are still obstacles when recording and reporting assets. The two Building Asset Performance Framework indicators used in this study, namely financial risk and risk of compliance with laws and regulations, show that local government organizations in Jombang Regency need to improve the accuracy of asset data collection, transparency of financial reports, and collaboration between stakeholders. These transformations and consistency are expected to increase the utilization of regional assets, such as land and buildings, in the following year, ensuring compliance with the Regent Regulation of Jombang Regency Number 52 of 2022 concerning Regional Asset Utilization. This research focuses on aspects directly related to asset management performance and local revenue potential, both of which have a direct impact on PAD achievement.